Improving Learning Outcomes of Writing Negotiation Texts Through the Application of Cooperative Learning Model - Waruwu, Pikiran (Jurnal Ilmu Multidisiplin Indonesia, 2024)
This study focuses on improving the ability to write negotiation texts for grade X A students of Bali Mandara State High School through the application of the Cooperative Learning model. Motivated by the problem of low mastery of negotiation text writing skills, this study uses a Classroom Action Research (PTK) approach with teachers and 29 students as subjects. The results showed that the application of Cooperative Learning effectively improved students' ability to write negotiation texts. In the first cycle, the average student score reached 78.15 with 65.52% of students achieving KKM. Cycle II showed a significant improvement, with an average score of 84.46 and 100% of students achieving KKM. The learning process is well structured, engages students in groups, motivates them to seek ideas outside the classroom, and encourages active participation and creativity.